Analysis of the Influence of Digitalization on UMKM Growth (Case Study of Bangka Belitung and Yogyakarta UMKM) - Rahmat ILYAS (Indonesia Strategic Sustainability, 2023)
UMKMs in Indonesia have an important role for the Indonesian economy. Currently, UMKM are an alternative to new employment opportunities to reduce the impact of unemployment in Indonesia. In addition, UMKM also play an important role in driving Indonesia's economic growth rate. During the ongoing Covid-19 pandemic occur moment In this case, UMKM activities experience various challenge at a time opportunity for growth Indonesian economy. Experienced challenges _ among them lack of introduction to digitization, adaptation to the development of the digital world and not have potential HR who can enter the digital world. study this is study descriptive quantitative, explained how The effect of digitalization on the growth of UMKM in the provinces of the Bangka Belitung Islands and Yogyakarta. Focus Study this UMKM in the provinces of Bangka Belitung and Yogyakarta Islands. the number of samples in this study 38 9 . The results of the research show that variable knowledge digitization take effect to UMKM growth , seen from t count value 8.131 > 1.967, value significant ie 0.000 < 0.05. variable digitization marketing take effect to see the growth of UMKM from t test results show 2.058 <t- table 1.967 value significance of 0.040 <0.05. Variable digitization sale take effect to UMKM growth with t value 9.100 <1.967, significance of 0.000 <0.05. variable digitization payment take effect to see the growth of UMKM from score t value 5.042 > 1.97 significance of 0.000 <0.05.